Building Interdisciplinary Leadership Skills among Health Practitioners in the Twenty-First Century: An Innovative Training Model - Negandhi, Preeti; Negandhi, Himanshu; Tiwari, Ritika; Sharma, Kavya; Zodpey, Sanjay P.; Quazi, Zahiruddin; Gaidhane, Abhay; Jayalakshmi N.,; Gijare, Meenakshi; Yeravdekar, Rajiv (Frontiers in Public Health, 2015)
Transformational learning is the focus of 21st century global educational reforms. In India there is a need to amalgamate the skills and knowledge of medical, nursing and public health practitioners and to develop robust leadership competencies among them. This initiative proposed to identify interdisciplinary leadership competencies among Indian health practitioners, and to develop a training program for interdisciplinary leadership skills through an Innovation Collaborative. Medical, nursing and public health institutions partnered in this endeavour. An exhaustive literature search was undertaken to identify leadership competencies in these three professions. Published evidence was utilized in searching for the need for interdisciplinary training of health practitioners, including current scenarios in inter-professional health education and the key competencies required. The interdisciplinary leadership competencies identified were: self-awareness, vision, self-regulation, motivation, decisiveness, integrity, interpersonal communication skills, strategic planning, team-building, innovation and being an effective change agent. Subsequently, a training program was developed and three training sessions were piloted with 66 participants. Each cohort comprised of a mix of participants from different disciplines. The pilot training guided the development of a training model for building interdisciplinary leadership skills and organizing interdisciplinary leadership workshops. The need for interdisciplinary leadership competencies is recognized. The long-term objective of the training model is integration into the regular medical, nursing and public health curricula, with the aim of developing interdisciplinary leadership skills among them. Although challenging, formal incorporation of leadership skills into health professional education is possible within the interdisciplinary classroom setting using principles of transformative learning.